Below-bandgap excitation of bulk semiconductors by twisted light - Quinteiro, Guillermo Federico (2010)
I theoretically investigate the excitation of bulk semiconductors by twisted light below the energy bandgap. To this end, I modify a well-known model of light-semiconductor interaction to account for the conservation of the momentum of light. I predict that the optical excitation produces a superposition of exciton-like states that undergo a complex center-of-mass motion. In addition, I show that the energy at which the absorption occurs is slightly different from that of pure excitons, due to the center-of-mass kinetic energy of the new states. Finally, I provide expressions for the induced polarization and electric current, which exhibit complex spatial patterns that mimic the twisted-light electric field. Copyright © 2010 EPLA.